2018
DOI: 10.1177/1477153518772000
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and pupil responses to discomfort glare from small, high-luminance light sources

Abstract: This study examined human subjective and pupil responses to small, high-luminance light sources seen against low-luminance backgrounds. Subjective judgements of glare using a seven-point rating scale and the change in pupil diameters following exposure to glare of 47 subjects were measured during evaluation of 36 conditions comprising three glare source luminances (20,000; 205,000; 750,000 cd/m2), two source positions (0°, 10°), two source sizes (10−5, 10−4 sr) and three background luminances (0.03; 0.3; 1 cd/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…It is experienced as visual discomfort without necessarily an impaired ability to see. Discomfort glare has been associated with fluctuations in pupil size 102,103 as well as contractions in the muscles surrounding the eye that may cause pain effects. 104 It is believed that the pupil, lens, facial and extra-ocular muscles are engaged in a constant pursuit of retinal image clarity, and this continuous muscle readjustment can cause discomfort, tension and pain.…”
Section: How Lighting Can Affect Human Healthmentioning
confidence: 99%
“…It is experienced as visual discomfort without necessarily an impaired ability to see. Discomfort glare has been associated with fluctuations in pupil size 102,103 as well as contractions in the muscles surrounding the eye that may cause pain effects. 104 It is believed that the pupil, lens, facial and extra-ocular muscles are engaged in a constant pursuit of retinal image clarity, and this continuous muscle readjustment can cause discomfort, tension and pain.…”
Section: How Lighting Can Affect Human Healthmentioning
confidence: 99%
“…A review of different methodologies that explored physiological measurement of discomfort glare was published in 2019 by Hamedani et al [11] Absolute pupil size seems to be more linked to background illumination rather than discomfort, with reported significant correlations between pupil size and discomfort rating [38,39], but weak correlations (r2 < 0.5). Relative pupil size seems more of interest as it takes into account baseline pupil size but correlations are similar (r2 = 0.43) [40]. Pupil size modification is the fastest process used by the eye to adapt to the light.…”
Section: Objective Measurements Of Discomfort Glarementioning
confidence: 99%
“…Research on blinking rate, palpebral aperture, and eye gaze has been also conducted but none demonstrated any strong relationship with glare rating [11,[38][39][40]. The most promising objective measurement of discomfort glare has been developed by Murray et al [45] using electromyogram around the eye, although the method is invasive and therefore has reduced applicability as a routine assessment in clinical settings.…”
Section: Objective Measurements Of Discomfort Glarementioning
confidence: 99%
“…Pupil size has been widely studied as an indicator of discomfort glare. Absolute and relative pupil sizes are linked to discomfort glare when measured with a rating scale [11][12][13] ; however, the correlations are weak (r 2 < 0.5). Some studies have not found any effect of iris pigmentation, 3,11 but Bennet 14 measured higher mean discomfort thresholds for brown eyes than blue eyes.…”
Section: Introductionmentioning
confidence: 99%